Effect of preexercise ingestion of modified amylomaize starch on glycemic response while cycling - Parks, R. B.; Angus, H. F.; King, D. S.; Sharp, R. L. (International Journal of Sport Nutrition and Exercise Metabolism, 2018)
Amylomaize-7 is classified as a resistant corn starch and is 68% digestible. When modified by partial hydrolysis in ethanol and hydrochloric acid its digestibility is 92%, yet retains its low glycemic and insulinemic properties. The purpose of this study was to characterize the metabolic response when modified amylomaize-7 or dextrose is consumed in the hour before exercise, and to compare the effect on performance of a brief high-intensity cycling trial. Ten male, trained cyclists were given 1 g/kg body mass of dextrose (DEX) or modified amylomaize-7 (AMY-7) or a flavored water placebo (PL) 45 min prior to exercise on a cycle ergometer. A 15-min ride at 60% Wmax was immediately followed by a self-paced time trial (TT) equivalent to 15 min at 80% Wmax. When cyclists consumed DEX, mean serum glucose concentration increased by 3.3 ± 2.1 mmol/L before exercise, compared to stable serum glucose observed for AMY-7 or PL. Glucose concentrations returned to baseline by pre-TT in all treatments. However, the mean post-TT glucose concentration of the DEX group was significantly lower than baseline, AMY-7, or PL. Serum insulin concentration increased nine-fold from baseline to preexercise in the DEX trial, whereas PL or AMY-7 remained unchanged. Time required to complete the performance trial was not significantly different between DEX, AMY-7 or PL. Preexercise ingestion of modified amylomaize-7 compared to dextrose resulted in a more stable serum glucose concentration, but did not offer a performance advantage in this high-intensity cycling trial.